2019
DOI: 10.1186/s40691-018-0161-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fashion vlogger attributes on product attitude and content sharing

Abstract: With the rapid development of Internet technology, various new media platforms have emerged consequently impacting many aspects of our lives (Kim and Jeon 2016). The emergence of various media and communication platforms changed the way people exchange information, turned then-existed one-way communication into two-way communication, and laid the foundation for the development various social media. Furthermore by the creation of a platform to share videos, video content is getting more popular, leading the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 25 publications
3
65
1
Order By: Relevance
“…YouTube vloggers refer to people who create a video blog or vlog by planning and appearing directly in the video. According to Choi and Lee (2019), vloggers have a common denominator with celebrities from the aspect that they approach audiences through videos, just as celebrities who contact the public via traditional media outlets. The difference is that vloggers designed the flow of video content themselves, not only serving as a model in the video.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…YouTube vloggers refer to people who create a video blog or vlog by planning and appearing directly in the video. According to Choi and Lee (2019), vloggers have a common denominator with celebrities from the aspect that they approach audiences through videos, just as celebrities who contact the public via traditional media outlets. The difference is that vloggers designed the flow of video content themselves, not only serving as a model in the video.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Following the informative/entertaining content dichotomy in advertising and previous research on blog content into consideration, this research parsimoniously evaluates the value viewers gain from the content with respect to its informative and entertaining nature. Third, expertise, credibility (Chapple and Cownie, 2017;Hill et al, 2017;Sakib et al, 2019), trustworthiness (Choi and Lee, 2019) and physical and social attractiveness (Chapple and Cownie, 2017;Liu et al, 2019) of the vloggers have been identified as important factors shaping consumers attitudes and behavior. Yet, this particular study examines the impact of authoritative knowledge on information satisfaction as similar to expertise, credibility and trustworthiness authoritative knowledge has also been suggested in literature to induce trust among blog readers (Doyle et al, 2012).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Subsequently, the user becomes a transmitter to share his/her experience about product consumption. According to previous studies, the positive attitude towards digital influencer content is linked to content sharing intention at social network (Choi & Lee, 2019). Based on the aforementioned literature, we postulate following hypotheses.…”
Section: New Consumption Behavior Model (Dual Aisas) Decision Processes and Hypotheses Developmentmentioning
confidence: 93%